2009
DOI: 10.1038/bmt.2008.446
|View full text |Cite
|
Sign up to set email alerts
|

BU and CY as conditioning regimen for autologous transplant in patients with multiple myeloma

Abstract: High-dose melphalan is considered the current standard of care among the preparative regimens used in peripheral blood autologous SCT (ASCT) for multiple myeloma (MM). We report the results of a single ASCT in 79 MM patients using the BU/CY conditioning regimen, with BU 1 mg/kg p.o. or 0.8 mg/kg i.v. every 6 h  16 doses, and CY 60 mg/kg per day i.v. for 2 days. ASCT was carried out in first (62%) or subsequent remission/refractory disease (38%). For an overall RR of 86%, 48 and 20 patients achieved PR and CR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…BU/CY conditioning regimen before ASCT was tried in advanced MM in 1994, and the author has indicated that this regimen was tolerable and effective in such patients [26]. In the following years, the BU/CY regimen was conducted by Amir A et al and G Talamo et al in their research, and similar outcomes were found [27,28]. Other scholars have added thiotepa and etoposide to the BU/CY regimen, and these studies have also obtained favorable results [14,29].…”
Section: Discussionmentioning
confidence: 93%
“…BU/CY conditioning regimen before ASCT was tried in advanced MM in 1994, and the author has indicated that this regimen was tolerable and effective in such patients [26]. In the following years, the BU/CY regimen was conducted by Amir A et al and G Talamo et al in their research, and similar outcomes were found [27,28]. Other scholars have added thiotepa and etoposide to the BU/CY regimen, and these studies have also obtained favorable results [14,29].…”
Section: Discussionmentioning
confidence: 93%
“…In fact, single‐agent HD‐Mel has replaced previous regimens that incorporated total body irradiation (TBI) because of similar survival and reduced toxic death rate . Moreover, the use of other conditioning chemotherapy regimens did not improve clinical outcomes compared to HD single‐agent melphalan, based on the published experiences of several groups , including our own .…”
Section: Four Traditional Schedules Of Hd‐mel 200 Mg/m2 With (A B) mentioning
confidence: 92%
“…The introduction of intravenous busulfan and therapeutic drug monitoring have ensured safer administration and resulted in tolerable toxicity profiles. Numerous studies in MM have used both oral and intravenous busulfan as a conditioning regimen in combination mostly with melphalan 8,11,12 but also with cyclophosphamide 13,14 , idarubicin 15 , thiotepa 16 , etoposide 17 , bortezomib 18 , carmustine 19 , and with total body irradiation 20 . However, single-agent intravenous busulfan with therapeutic dose monitoring has not been studied as a conditioning regimen for MM.…”
Section: Introductionmentioning
confidence: 99%